The Influence of Knowledge Sharing, Work Life Balance, and Work Professionalism on Employee Performance My Lova Bengkulu - Tiani, Kiki Elva; Kusuma, Merta; Ekowati, Sri; Yulinda, Ade Tiara (Proceedings Series on Social Sciences & Humanities, 2025)
This study aims to examine the Influence of Knowledge Sharing, Work-Life Balance, and Work Professionalism on the performance of employees at My Lova Bengkulu. This research was conducted in March 2025 until completion. The sample in this study consisted to 40 respondents who were employees at My Lova Bengkulu Store. The sampling technique used was total sampling.This research employed a quantitative method with multiple linear regression analysis using SPSS 25 for windows. Based on the results of multiple regression analysis, the regression equation obtained is: Y = 14.724 + 0.359 (X1) + 0.275 (X2) + 0.465 (X3), with the coefficient of determination (R2) = 0.660, indicating that 66% of the variation in employee performance (Y) is explained by the independent variables. The findings and hypotheses of this study indicate that knowledge sharing has a positive and significant effect on employee performance; work-life balance has a positive and significant effect on empoyee performance; and work professionalism also has a positive and significant effect on the performance of employees at My Lova Bengkulu.